prove: (1) cot square A.cosec square B-cot square B.cosec square A= cot squareA-cot squareB (2) 2sin square theta+cos square theta= 2 under root. 2sin theta.cos theta

Asked by sonali garg | 11th Sep, 2013, 09:15: PM

Expert Answer:

Pls ask one question at a time. The solution to your first question is as follows:

LHS

= cot2A. cosec2B - cot2B. cosec2A

= cot2A. (1 + cot2B) - cot2B. (1 + cot2A)

= cot2A + cot2A cot2B - cot2B - cot2A cot2B

= cot2A - cot2B

= RHS

Answered by  | 11th Sep, 2013, 10:25: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.